Economic contribution of cedar wood (Cedrela odorata L.) as a shade tree in coffee plantations in Pérez Zeledón, Costa Rica - Calvé Jarque, Sergio (2020)
The study determined the economical contribution of cedar wood (Cedrela odorata L.) in agroforestry systems with coffee in Costa Rica. 26-coffee farms associated to CoopeAgri R.L. in Pérez Zeledón county. Cedar has been planted as a shade tree in coffee production areas in this county, with an average density of 214 trees/ha, which corresponds to a 7x7 m spacing, but it varies from 70 to 700 trees. Cedar in coffee plantations registers a growth rate of 2.5 cm/year in diameter, which allows it to reach 40 cm in dbh at 16 years of age. Planting cedar in coffee areas produce economical incomes from wood sales of approximately $ 5000ha-1 and a total commercial volume of 100 m3 ha-1 in 16 years. From this amount 60 % has commercial value for sawmill industry in its 6 m merchantable stem. Meanwhile, fuelwood represents 35 % of total volume, but only 8 % of the total tree value. Good silvicultural management techniques, like crown prunning and Hypsipyla grandella attack prevention, with an initial density of 277 trees (6 x 6 m that will be thinned to 12 x 6 m at age 8) may increase the wood value up to $7000ha-1. Cedar trees planted in agroforestry systems with coffee, is an excellent option that enhances higher incomes for producers.